Digital twin-driven vibration state monitoring method for gear transmission systems - TANG Xianju; HU Zhi’an; SHE Yixi; HAN Bing; SHI Zhenfu (Jixie chuandong)
ObjectiveThe vibration analysis is an effective and widely used technology for monitoring the state of the rotating machinery. To better manage the health condition of various components in gear transmission systems, a vibration state monitoring framework for gear transmission systems based on the digital twin technology was proposed.MethodsFirstly, the functionality and logical relation of each module in this technology framework were introduced from the physical layer, the data layer, the model layer, and the application layer, respectively. Secondly, the construction of the performance model and the behavior model for the gear transmission system was detailed. The performance model was used to simulate vibration signals, while the behavior model was utilized for updating the digital twin model. Finally, using a two-stage fixed-axis gear transmission system as an example, its digital twin system was established. Theoretical analysis and verification of various key technologies were conducted.ResultsThe digital twin system achieves online vibration monitoring of the gear transmission system. The simulation response of the digital twin model shows close agreement with the measured vibration data, validating the effectiveness of both the performance and behavior models. This study provides valuable data support for the fatigue life prediction and reliability assessment of key components in the gearbox, contributing to the advancement of digital twin technology in the monitoring of rotating machinery.